High strain-rate compression behavior of woven CF/PEEK thermoplastic composites at the glassy state and high-elastic state. (1st December 2022) - Pan, Zhongxiang; Yang, Chengcai; Huang, Shuwei; Wang, Mingling; Wu, Zhenyu; Gu, Bohong
Highlight: Air flow heating without tank is reliable and effective for drastic impact loads. Mechanics of woven CF/PEEK is more sensitive to temperature than strain rate. Ultimate service temperature significantly influences impact dynamic behavior. Brittle-Loose transition of damage modes were found from glassy to high-elastic state. Failure modes at high temperature were verified by micro-scale characterization. Abstract: A reliable hot air-flow heating approach is creatively carried out for high strain rate tests without environment tank. The out-of-plane and in-plane compression of carbon fiber reinforced polyetheretherketone (CF/PEEK) woven composites are investigated from 400 to 4000/s at the glassy state and high-elastic state. The real-time and in-situ deformation and failure process of the composite specimens under the extreme thermo-mechanical loads are successfully captured, which can reflect the impact dynamic behavior of the material near the ultimate service temperature. Empirical laws for mechanical index of the woven composites are given. The results reveal that the thermal softening effect outperforms the strain-rate strengthening effect. For out-of-plane impact at low strain rates, damage mode transitions from the interface and matrix cracking at glassy state to the "parallel" shear and fiber extrusion at high-elastic state. Under high strain rates, it reveals the "fragmented" shear mode at glassy state. For in-plane impact, the temperature effect leads to the failure mode changing from the delamination and local shear to the mixed feature of kinking bands, delamination, and multiple-band shear with "bulge" behavior. And the multiple-band shear and delamination are more likely to occur along the in-plane direction as the strain rate increased. Graphical abstract: Image, graphical abstract